Politics for sustainable consumption and production patterns - Scholl, Gerd; Rubik, Frieder (Ökologisches Wirtschaften - Fachzeitschrift, 2008)
Einführung in das Schwerpunktthema
Keywords: Sustainable Consumption; Sustainable Production; Policies